THE HEALTH-RELATED QUALITY OF LIFE IN MOTHERS OF SURVIVING DEAF BLIND ADULT CHILDREN WITH CONGENITAL RUBELLA SYNDROME IN THE UNITED STATES - Armstrong, Normadeane (European Scientific Journal, ESJ, 2015)
The purpose of this study was to determine the health related quality of life (HRQOL) of mothers of surviving deaf-blind adult children with congenital rubella syndrome (CRS) and the relationship of factors that influence it. This study uses a cross sectional design with all of the study participants having surviving CRS children born from the 1963-1965 epidemic. Analysis revealed: 1). Maternal CSI scores were significantly associated with the HRQOL F (13, 273) = 67.175 p< .001. Mothers who experienced high levels of caregiver stress had a poorer overall quality of life than those with lower levels of stress. 2).The deaf-blind adult child’s with CRS functional ability was significantly associated with the maternal HRQOL F (22, 263) = 17.03 p< .001. Mothers of adult deaf blind children needing care had poorer overall quality of life than those more independent. 3). Communication methods were significantly associated with the HRQOL. Communication with Sign Language (M= 80.39, SD= 20.8) demonstrated better overall maternal HRQOL scores than those with gestures (M= 31.49, SD= 32.57), F (8, 277) = 17.471, p < .001. 4). 4). Behaviors were significantly associated with the HRQOL with the largest difference between adult- children demonstrating no apparent behavior (M= 89.77, SD= 11.7) to those presenting aggressive behavior (M= 30.95, SD= 30.37), F (7, 279) =21.130 p < .001. As the prevalence of children with disabilities continues to increase, so does the demand for professionals who understand the unique needs of caregivers. Professionals must understand the impact special needs have on the mother and by extension, the family, and be able to provide the care and resources needed to support the continued care.